Cascade-activatable NO release based on GSH-detonated "nanobomb" for multi-pathways cancer therapy. (March 2022) - Feng, Yi; Zhang, Hanxi; Xie, Xiaoxue; Chen, Yu; Yang, Geng; Wei, Xiaodan; Li, Ningxi; Li, Mengyue; Li, Tingting; Qin, Xiang; Li, Shun; You, Fengming; et al.
Abstract: Therapeutic approaches of combining conventional photodynamic therapy (PDT) with other adjuvant treatments to sensitize PDT represent an appealing strategy. Herein, a novel synergetic "nanobomb" strategy based on glutathione (GSH)-responsive biodegradation was proposed to effectively destroy tumors expeditiously and accurately. This "nanobomb" was rationally constructed via the simultaneous encapsulation of methylene blue (MB) and l -arginine (L-Arg) into polyethylene glycol (PEG) modified mesoporous organosilicon nanoparticles (MON). The resulting L-Arg/MB@MP initially exhibited prolonged blood circulation, improved bioavailability, and enhanced tumor accumulation in mice after tail vein injection according to the pharmacokinetic investigations, before the nanoparticles were entirely excreted. Under laser irradiation, L-Arg/MB@MP produced remarkable reactive oxygen species (ROS) directly for PDT therapy, while a portion of ROS may oxidize L-Arg to generate nitric oxide (NO) not only for gas therapy (GT) but also serve as a biological messenger to regulate vasodilation to alleviate the tumor hypoxia. Subsequently, the rapidly released NO was further oxidized to reactive nitrogen species, which together with ROS promote immunogenic cell death by inducing G2/M cell-cycle arrest and apoptosis in cancer cells, and eventually resulting in enhanced anti-tumor immune responses. Moreover, the GSH depletion in tumor tissues induced by L-Arg/MB@MP biodegradation can cooperate with GT to amplify the therapeutic effect of PDT. These results demonstrate that this "nanobomb" provides new ideas for clinical translation to treat tumor patients in terms of synergistic PDT-GT nanotherapy in hypoxic-solid tumors. Graphical abstract: Image 1 Highlights: Here, a novel GSH-responsive nanoplatform (L-Arg/MB@MP) was developed to combine nitric oxide (NO)-based gas therapy (GT) to amplify PDT. The GSH-responsive property of L-Arg/MB@MP leaded to rapid biodegradation of the nanoparticles and controlled drug release. L-Arg/MB@MP generated considerable ROS and NO for PDT-GT to relieve the tumor hypoxia, consequently activating antitumor immunity.